PENERAPAN BERMAIN KREASI MELANGKAH DALAM MENGEMBANGKAN MOTORIK KASAR ANAK KELOMPOK A DI TAMAN KANAK-KANAK AISYIYAH - Ulfa, Siti Maria (Universitas Muria Kudus, 2024)
The aim of this research is to find out how to improve children's gross motor skills through creative step play at Aisyiyah Kindergarten.The research method used is classroom action research with a cycle consisting of planning, action, observation and reflection. The research subjects were 20 group A children at Aisyiyah Kindergarten (10 boys and 10 girls). The research location was Aisyiyah Kindergarten with a sample of all group A children in Aisyiyah Kindergarten. Data collection techniques are carried out through direct observation. The data validation technique used in this research is method triangulation and source triangulation. The data analysis technique used in this research is qualitative descriptive analysisThe results of the research show that the application of creative play steps in developing children's physical motor skills, showing a very significant will in achieving the success target of this research. The success obtained is as follows: The success obtained in developing children's physical motor skills can develop well until it reaches 75%, as the achievement of the success target has been determined. Through the application of creative step play, children can improve their gross motor skills.